Structural damage detectability using modal and ultrasonic approaches. (May 2016) - Blachowski, B.; Swiercz, A.; Gutkiewicz, P.; Szelążek, J.; Gutkowski, W.
Abstract: An experimental and analytical study of the relation between local defect, in a steel structure, and its higher frequencies and higher modes is discussed. The structure is a plane steel frame, assembled of beams, joined together with bolted connections. Removing some bolts from a given connection simulates the damage. In the experiment, an impulse force induced structural vibrations. Effects of vibrations were shown by data from gages, measuring accelerations with a high accuracy. From the data, it could be observed, that mode shapes, for the healthy and damaged structures didn't show any differences for low frequencies. Only modes around thirteen showed significant gap between picks of Frequency Response Functions, for healthy and damaged frame. Moreover, looking at mode shapes, it could be observed that structural configuration may have some influence on defects to be observable. This aspect is discussed in a separate section. The experiment performed on the whole structure allows finding the place where the defect is localized. However, it can't give detailed information on the defect itself, here defect of a bolt. For finding it, an ultrasonic measurement of pre-tensioning forces in bolts was applied. It allowed not only to determine stresses in the bolt, but also to verify, if in the process of assembling the structure was not pre-stressed.